Diagnosis dan tatalaksana rinosinusitis maksilaris odontogenik yang meluas sampai etmoid dan frontal: laporan kasus - Agus Santosa; Nyoman Dian Permata Sari; Ida Bagus Semara Putra; Dewa Ayu Putu Sri Masyeni (DiscoverSys Inc., 2021)
Background: Sinusitis is an inflammatory process in the nasal mucosa, especially in the paranasal sinuses. Sinusitis problems are important and need special attention in cases of sinusitis that do not improve after being given conventional therapy. The purpose of this paper is to establish the diagnosis and management of odontogenic maxillary rhinosinusitis that extends to the ethmoid and frontal areas.Case presentation: A male patient, aged 22 years, came to the ENT clinic at Mangusada Hospital, Badung. Based on the history, physical examination, supporting examination in the form of CT-scan so that it was diagnosed as chronic rhinosinusitis et causa odontogenic which extends to the ethmoid and frontal. The treatment chosen was surgery in the form of Functional Endoscopic Sinus Surgery (FESS) and septorhinoplasty because in this case the patient had complications and did not respond to medical therapy. Postoperative evaluation, complaints of smelly mucus, nasal congestion and headache were not felt.Conclusion: The diagnosis of chronic rhinosinusitis et causa odontogenic which extends to the ethmoid and frontal based on CT-Scan and the treatment given to the patient in the form of FESS and septorhinoplasty. Latar belakang: Sinusitis merupakan proses inflamasi pada mukosa hidung, lebih khususnya pada sinus paranasal. Masalah sinusitis menjadi penting dan perlu perhatian khusus pada kasus sinusitis yang tidak membaik setelah diberikan terapi konvensional. Tujuan penulisan ini adalah untuk menegakkan diagnosis dan penatalaksan rinosinusitis maksilaris odontogenik yang meluas sampai etmoid dan frontal.Presentasi kasus: Seorang pasien laki-laki, berusia 22 tahun datang ke poli THT RS Mangusada, Badung. Berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan penunjang berupa CT-scan sehingga didiagnosis sebagai rinosinusitis kronis et causa odontogenic yang meluas sampai etmoid dan frontal. Penatalaksanaan yang dipilih adalah pembedahan berupa Functional Endoscopic Sinus Surgery (FESS) dan septorhinoplasti, karena pada kasus ini pasien mengalami komplikasi dan tidak memberikan respon dengan terapi medikamentosa. Evaluasi pasca operasi, keluhan ingus berbau, hidung tersumbat dan nyeri kepala sudah tidak dirasakan.Kesimpulan: Diagnosis rinosinusitis kronis et causa odontogenic yang meluas sampai etmoid dan frontal berdasarkan dari CT-Scan dan tatalaksana yang diberikan pada pasien berupa FESS dan septorhinoplasti.